Quality of life and pain relief in men with metastatic castration-resistant prostate cancer on cabazitaxel: the non-interventional ‘QoLiTime’ study - Hofheinz, Ralf-Dieter (BJU international, 2017)
Objective: To examine health-related quality of life (QoL) in men with metastatic castration-resistant prostate cancer (mCRPC) on cabazitaxel. Patients and Methods: Men with mCRPC receiving cabazitaxel (25 mg/m², every 3 weeks) and 10 mg/day oral prednis(ol)one were enrolled (2011-2014) in the non-interventional prospective ‘QoLiTime’ study. Primary outcome was change in QoL (European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire 30-item) with respect to prostate-specific antigen (PSA) response after four cycles of cabazitaxel. Secondary outcomes included occurrence of adverse events (AEs). Results: Of 527 men, 348 received four cycles of cabazitaxel and 266 had the necessary PSA level measurements. After four cycles, 92 (34.6%) men had a PSA level decrease ≥50% (responders). QoL remained stable throughout the study (P = 0.62). Change in QoL did not differ between responders and non-responders (P = 0.69). Change in PSA level and global health status between baseline and four cycles showed an inversely proportional relationship (correlation coefficient -0.14; 95% confidence interval -0.26 to -0.01; P = 0.03), with increasing PSA level corresponding to lower health status. Responders showed no change in physical functioning vs baseline (-1.75, P = 0.12); non-responders showed a reduction vs baseline (-7.00, P < 0.001) and responders (P = 0.05). Responders showed an improvement in pain vs baseline (-7.61, P = 0.05) and vs non-responders (P = 0.01). AEs occurred in 292 patients (55.4%), most commonly anaemia (16.5%), fatigue (12.3%) and diarrhoea (11.8%). Neutropenia and febrile neutropenia were reported in 3.8% and 3.6% of patients, respectively. Conclusion: Prostate-specific antigen level response was associated with stable physical functioning and improvement in pain. Symptom increases were seen in areas typical of chemotoxicity, but QoL was maintained.